Trabalhadores em Mondaí-SC (1980-2020): experiências de trabalho na indústria moveleira - Silva Junior, Ernesto da (2022)
This research sought to understand the work experiences in the region of Mondaí-SC (19802020). With oral interviews, the subjects who took a leading role in the narrative were workers who moved between work in the countryside and in the city. The general orientation that led to writing was to think about how the subjects feel the relations of exploration and the moment in which they dispute spaces.